Difference between revisions of "1975 AHSME Problems/Problem 1"

(Created page with "==Solution== Calculating, we find that <math>\frac {1}{2 - \frac {1}{2 - \frac {1}{2 - \frac12}}} = \frac {1}{2 - \frac {1}{2 - \frac {2}{3}}} = \frac {1}{2 - \frac {3}{4}}...")
 
m (Solution)
Line 1: Line 1:
 
==Solution==
 
==Solution==
 +
Solution by e_power_pi_times_i
  
  
 
+
Calculating, we find that <math>\frac {1}{2 - \frac {1}{2 - \frac {1}{2 - \frac12}}} = \frac {1}{2 - \frac {1}{2 - \frac {2}{3}}} = \frac {1}{2 - \frac {3}{4}} = \frac {1}{\frac {5}{4}} = \boxed{\textbf{(B) } \dfrac{4}{5}}</math>.
Calculating, we find that <math>\frac {1}{2 - \frac {1}{2 - \frac {1}{2 - \frac12}}} = \frac {1}{2 - \frac {1}{2 - \frac {2}{3}}} = \frac {1}{2 - \frac {3}{4}} = \frac {1}{\frac {5}{4}} = \boxed{\textbf{(B) } \dfrac{4}{5}</math>.
 

Revision as of 12:51, 15 December 2016

Solution

Solution by e_power_pi_times_i


Calculating, we find that $\frac {1}{2 - \frac {1}{2 - \frac {1}{2 - \frac12}}} = \frac {1}{2 - \frac {1}{2 - \frac {2}{3}}} = \frac {1}{2 - \frac {3}{4}} = \frac {1}{\frac {5}{4}} = \boxed{\textbf{(B) } \dfrac{4}{5}}$.

Invalid username
Login to AoPS